Effect of Diet Type and Added Copper on Growth Performance, Carcass Characteristics, Energy Digestibility, Gut Morphology, and Mucosal mRNA Expression of Finishing Pigs - K. F. Coble; D. D. Burnett; R. D. Goodband; J. M. Gonzales; J. Usry; M. D. Tokach; J. R. Pluske; J. M. DeRouchey; J. C. Woodworth; S. S. Dritz; J. R. Flohr; M. A. Vaughn (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 757 pigs (PIC 337 × 1050, initially 60.8 lb) were used to determine the effects of added Cu (TBCC, tribasic copper chloride, IntelliBond C; Micronutrients, Inc., Indianapolis, IN) and diet type on growth performance, carcass characteristics, energy digestibility, gut morphology, and mucosal mRNA expression of finishing pigs. Pens of pigs were allotted to 1 of 4 dietary treatments, balanced on average pen weight in a randomized complete-block design with 26 to 28 pigs per pen and 7 replications per treatment. Treatments were arranged as a 2 × 2 factorial with main effects of diet type, a corn-soybean meal-based diet or a high by-product diet with 30% distillers dried grains with solubles (DDGS) and 15% bakery meal (by-product), and with or without added Cu (0 or 150 ppm added Cu). There were no Cu × diet type interactions for growth performance. Overall, neither added Cu nor diet type influenced growth performance. Pigs fed the by-product diet had decreased carcass yield (P = 0.007) and HCW F/G (P = 0.013), and tended to have decreased HCW (P = 0.067) and HCW ADG (P = 0.056) compared to pigs fed the corn-soybean meal-based diet. A Cu × diet type interaction (P<0.05) existed for DM and GE digestibility during the early finishing period as added Cu improved digestibility of DM and GE in the corn-soybean mealbased diet, but not in the by-product diet. During the late finishing period, added Cu increased DM and GE digestibility (P = 0.060), while pigs fed the by-product diet had decreased DM and GE digestibility (P = 0.001). For gut morphology, pigs fed added Cu had decreased crypt depth (P = 0.017) in the distal small intestine. Relative mRNA expression of intestinal fatty acid binding protein (iFABP) was decreased (P = 0.032) in pigs fed added Cu. In summary, adding 150 ppm added Cu or including 30% DDGS and 15% bakery meal into a corn-soybean meal-based diet did not influence growth performance. However, HCW ADG and HCW G/F were reduced in pigs fed the by-product diet. Only minor differences in gut morphology or mRNA expression were observed from pigs fed diets with high levels of Cu or by-products compared to those fed a corn-soybean meal-based diet.
Keywords: by-product; copper; finishing pigs; gene expression